Early Detection of Myocardial Involvement in Thalassemia Intermedia Patients: Multiparametric Mapping by Magnetic Resonance Imaging - Meloni, Antonella; Pistoia, Laura; Garamella, Davide; Parlato, Alessandro; Positano, Vincenzo; Ricchi, Paolo; Casini, Tommaso; De Marco, Emanuela; Corigliano, Elisabetta; Borsellino, Zelia; Visceglie, Domenico; De Caterina, Raffaele; et al. (Journal of magnetic resonance imaging, 2025)
Background No study has assessed myocardial T1 and T2 values in patients with beta‐thalassemia intermedia (β‐TI). Purpose To assess the prevalence of myocardial involvement in β‐TI patients by T2* relaxometry and native T1 and T2 mapping and to determine the correlation of myocardial relaxation times with demographic and clinical parameters. Study Type Prospective matched‐cohort study. Subjects 42 β‐TI patients (27 females, 39.65 ± 12.32 years), enrolled in the Extension‐Myocardial Iron Overload in Thalassaemia Network, and 42 age‐ and sex‐matched healthy volunteers (27 females, 40.01 ± 11.36 years) and thalassemia major (TM) patients (27 females, 39.27 ± 11.57 years). Field Strength/Sequence 1.5 T/multi‐echo gradient echo, modified Look‐Locker inversion recovery, multi‐echo fast‐spin‐echo, cine balanced steady‐state‐free precession, and late gadolinium enhancement (LGE) sequences. Assessment Hepatic, pancreatic, and left ventricular (LV) T2* values, LV native T1 and T2 values, biventricular ejection fractions and volumes, and presence and extent of replacement myocardial fibrosis. Statistical Tests Comparisons between two groups were performed with two‐sample t tests, Wilcoxon's signed rank tests, or χ2 testing. Correlation analysis was performed using Pearson's or Spearman's test. P < 0.05 was considered statistically significant. Results β‐TI patients had significantly higher LV T2 values than healthy subjects (56.84 ± 4.03 vs. 52.46 ± 2.50 msec, P < 0.0001) and significantly higher LV T1 values than TM patients (1018.32 ± 48.94 vs. 966.66 ± 66.47 msec, P < 0.0001). In β‐TI, female gender was associated with significantly increased LV T1 (P = 0.041) and T2 values (P < 0.0001), while splenectomy and presence of regular transfusions were associated with significantly lower LV T1 values (P = 0.014 and P = 0.001, respectively). In β‐TI patients, all LV relaxation times were significantly correlated with each other (T2*‐T1: P = 0.003; T2*‐T2: P = 0.003; T1‐T2: P < 0.0001). Two patients with a reduced LV T2* also had a reduced LV T1, while only one had a reduced LV T2. Three patients had a reduced LV T1 but a normal LV T2*; 66.7% of the patients had an increased LV T2. All LV relaxation times were significantly correlated with pancreas T2* values (T2*: P = 0.033; T1: P < 0.0001; T2: P = 0.014). No LV relaxation time was associated (P > 0.05) with hepatic iron concentration, biventricular function parameters, or LGE presence. Conclusion The combined use of all three myocardial relaxation times has potential to improve sensitivity in the detection of early/subclinical myocardial involvement in β‐Tl patients. Level of Evidence 2 Technical Efficacy Stage 2